2013
DOI: 10.1096/fj.13-229211
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen‐related receptor‐α (ERRα) deficiency in skeletal muscle impairs regeneration in response to injury

Abstract: The estrogen-related receptor-α (ERRα) regulates mitochondrial biogenesis and glucose and fatty acid oxidation during differentiation in skeletal myocytes. However, whether ERRα controls metabolic remodeling during skeletal muscle regeneration in vivo is unknown. We characterized the time course of skeletal muscle regeneration in wild-type (M-ERRαWT) and muscle-specific ERRα(-/-) (M-ERRα(-/-)) mice after injury by intramuscular cardiotoxin injection. M-ERRα(-/-) mice exhibited impaired regeneration characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 51 publications
0
68
0
Order By: Relevance
“…9B). However, muscle levels of ERR␣, which has many overlapping functions with ERR␥, enhances PGC-1␣ signaling (35), and is involved in muscle repair (36), were elevated in the muscle of FKBP12D mice (Fig. 9C).…”
Section: Resultsmentioning
confidence: 99%
“…9B). However, muscle levels of ERR␣, which has many overlapping functions with ERR␥, enhances PGC-1␣ signaling (35), and is involved in muscle repair (36), were elevated in the muscle of FKBP12D mice (Fig. 9C).…”
Section: Resultsmentioning
confidence: 99%
“…The knockout of ERRα in skeletal muscle causes no phenotypic change in the basal state [53] [54]. However, in a cardiotoxin induced injury model, its deficiency reduces mitochondrial activity and impairs muscle regeneration [54]. …”
Section: Skeletal Musclementioning
confidence: 99%
“…In contrast some studies show that AMPK inhibits myoblast differentiation though PGC1α transcription, and demonstrates that AICAR-induced AMPK phosphorylation reduces differentiation of myoblasts into myotubes through PGC1α transcription [19]. Regeneration in CTX-treated tibialis anterior muscle was dramatically impaired in mice treated with AICAR [45]. Here, we showed that AMPK activation by CaMKK2 (Figure 5A) in C2C12 cells was accompanied by an elevation of PGC1α expression (Figure 6A,B) and a suppression of myoblast differentiation (Figure 3A–C), while AMPK inactivation by the knockdown of CaMKK2 expression (Figure 4E) in C2C12 cells was accompanied by a reduce in PGC1α expression (Figure 6C,D) and an increase in myoblast differentiation (Figure 4G,H,I).…”
Section: Discussionmentioning
confidence: 99%